DEVELOPMENT OF A POCKETBOOK OF PARENTAL ASSISTANCE TO STIMULATE CHILDREN'S SOCIAL-EMOTIONAL DEVELOPMENT IN THE DIGITAL AGE - Yuniarni, Desni (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2024)
The rapid development of digital technology causes parents to know how to use this technology to have a positive impact on the social-emotional development of their children. The purpose of this study is to develop a pocket book for parents that contains how to provide assistance to children in optimizing aspects of their social-emotional development in the digital era. The type of research used is research and development using a 4D model (Four-D) from Hiagarajan. The subjects of the study were ECCE teachers. The source of research data is ECCE lecturers with undergraduate education in ECCE to obtain material expert validation data and ECCE teachers to obtain media expert validation data. The methods used are interview and questionnaire methods. The data analysis techniques used in this study are qualitative and quantitative descriptive analysis techniques. The results showed that this pocketbook is worth using after getting input.